PERNIKAHAN MELALUI TELEPON DAN REFORMASI HUKUM ISLAM DI INDONESA - Asnawi, Habib Shulton (Al-Mazaahib: Jurnal Perbandingan Hukum, 2012)
Islamic law is universal. The law must be developed in accordance with socialneeds, as well as the fiqh rule that "the law change with the changing times andchanging times". Islamic law in reality is not idealistic yet and not seem toanticipate the changing and tend to be far from justice. For example, the oldproduct of Islamic law states that marriage or consent granted shall be carriedout in a single chamber. Reason or ‘illat of law of one chamber is to maintaincontinuity and confidence witness against two parties are performing thecontract. Social development of the people of Indonesia, especially in the field oftechnology is currently growing rapidly. Among the legal issues that are biasedtechnological progress is the marriage by the phone. This issue raises the prosand cons among Indonesian scholars. Differences of opinion are based ondifferent interpretations of the concept of the unity of the assembly (ittih}a>dulmajlis) in a marriage ceremony. Therefore we need the rule of law in order to fillthe legal vacuum due to differences of opinion. It takes a good legalconstruction, which can accommodate the interests of modern society.